Highly efficient PLEDs based on poly(9, 9-dioctylfluorene) and Super Yellow blend with Cs2CO3 modified cathode. Issue 1 (November 2015) - Hassan, M.U.; Liu, Yee-Chen; Hasan, Kamran ul; Butt, H.; Chang, Jui-Fen; Friend, R.H.
Graphical abstract: Highlights: Efficient polymer light emitting diodes obtained by using blend of two polymers poly(9, 9-dioctylfluorene) (F8) and a poly( para -phenylenevinylene) (PPV) copolymer Super Yellow (SY). Large difference between the highest occupied molecular orbital (HOMO) levels of both polymers offers hole traps, resulting in pushing the radiative recombination within the bulk, away from the cathode – the cathode quenching effects are minimized. Cs2 CO3 interlayer at cathode surface enhances the electron injection, which always pushes the emission zone further away from the cathode surface and results in further enhancement in the efficiency. Abstract: Polymer light emitting diodes (PLEDs) based on the blend of 90% poly(9, 9-dioctylfluorene) (F8) and 10% Super Yellow (SY) were used as the emissive layer and it exhibited high luminous efficiency up to ∼27 cd A −1 . Hole-trapping nature native to the proposed blend system and efficient electron injection via Al/Ca/Cs2 CO3 cathode was used against the conventional ITO/PEDOT:PSS anode which provided a well-balanced charge transport across the emissive layer. Thereby, the scheme maximizes the radiative recombination of these excitons within the bulk and away from the cathode. Consequently, non-radiative quenching effects at the cathode surface were avoided which resulted in ultrahigh efficiency of such devices.